2017
DOI: 10.1515/sbe-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Work Meaningful

Abstract: Abstract:Most organizations nowadays have the required resources and should offer an appropriate culture to provide each employee with the opportunity and context to develop the feeling of meaningful work. The managers and organizational leaders should be the first to recognize and perceive the work they do as being important. In this article, we examine the current development of the study of the nature, causes, and consequences of meaningful work, and we offer ideas of research opportunities regarding the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
2
4
0
1
Order By: Relevance
“…Studies have found that employees who work under the coordination of a transformational leader experience meaningful work, which contributes to their psychological well-being (Grama & Todericiu, 2017). In a study by Arnold et al, well-being was measured by the experience of positive emotions and general mental health (Liyanage Grama, 2020& Todericiu, 2017. The findings of this study indicate that transformational leadership positively impacts employees' well-being (Gauche et al, 2017).…”
Section: The Relationship Between Transformational Leadership and Emp...mentioning
confidence: 60%
See 2 more Smart Citations
“…Studies have found that employees who work under the coordination of a transformational leader experience meaningful work, which contributes to their psychological well-being (Grama & Todericiu, 2017). In a study by Arnold et al, well-being was measured by the experience of positive emotions and general mental health (Liyanage Grama, 2020& Todericiu, 2017. The findings of this study indicate that transformational leadership positively impacts employees' well-being (Gauche et al, 2017).…”
Section: The Relationship Between Transformational Leadership and Emp...mentioning
confidence: 60%
“…Empirical research has shown that transformational leadership, which involves inspiring and motivating employees to achieve their full potential, positively affects employee well-being (Jacobs et al, 2013). Studies have found that employees who work under the coordination of a transformational leader experience meaningful work, which contributes to their psychological well-being (Grama & Todericiu, 2017). In a study by Arnold et al, well-being was measured by the experience of positive emotions and general mental health (Liyanage Grama, 2020& Todericiu, 2017.…”
Section: The Relationship Between Transformational Leadership and Emp...mentioning
confidence: 99%
See 1 more Smart Citation
“…İnsanlar için işin önemini ortaya koymayı amaçlayan çok sayıda araştırma yürütülmüş ve yürütülmeye devam edilmektedir. Zamanla işin anlamlılığı konusunun gittikçe önem kazanmaya ve ilgi toplamaya başladığı görülmektedir (Grama ve Todericiu, 2017). İşin anlamlı olarak algılanmasının ve bir motivasyon aracına dönüşmesinin en çok STK'lar için önemli olduğu ifade edilmektedir.…”
Section: Introductionunclassified
“…Numerous studies have been conducted and continue to be conducted, aiming to investigate the importance of work for people. Recently, it is seen that the subject of meaningfulness of work has started to gain importance and attract attention (Grama ve Todericiu, 2017).Because it is seen that the volunteers are mostly motivated by spiritual elements and the importance, purpose, and values of the work. This situation reveals that meaningful work requires a good person-organization fit (Wang and Seifert, 2021).In the workplace, it is expected that the meaningfulness, importance, and value attributed to the work will increase as a result of person-organization fit.…”
Section: Introductionmentioning
confidence: 99%